Advanced energy materials for flexible batteries in energy storage: A review. (8th November 2020) - Kong, Long; Tang, Cheng; Peng, Hong‐Jie; Huang, Jia‐Qi; Zhang, Qiang
Abstract: Smart energy storage has revolutionized portable electronics and electrical vehicles. The current smart energy storage devices have penetrated into flexible electronic markets at an unprecedented rate. Flexible batteries are key power sources to enable vast flexible devices, which put forward additional requirements, such as bendable, twistable, stretchable, and ultrathin, to adapt mechanical deformation under the working conditions. This review summarizes the recent advances in construction and configuration of flexible batteries and discusses the general metrics to benchmark various flexible batteries with different materials and chemistries. Moreover, we present advanced prototype flexible batteries developed by some companies to afford general envision of the technological status. Lastly, the critical points are summarized in the development of flexible batteries and remaining challenges are also presented for the future design of flexible batteries in practical perspectives. Abstract : Flexible batteries are key power sources to smart energy storage. This review summarizes the recent advances of flexible batteries and affords perspectives on the design of efficient battery components and configurations.